2015
DOI: 10.3934/mbe.2015.12.1237
|View full text |Cite
|
Sign up to set email alerts
|

Treatment strategies for combining immunostimulatory oncolytic virus therapeutics with dendritic cell injections

Abstract: Oncolytic viruses (OVs) are used to treat cancer, as they selectively replicate inside of and lyse tumor cells. The efficacy of this process is limited and new OVs are being designed to mediate tumor cell release of cytokines and co-stimulatory molecules, which attract cytotoxic T cells to target tumor cells, thus increasing the tumor-killing effects of OVs. To further promote treatment efficacy, OVs can be combined with other treatments, such as was done by Huang et al., who showed that combining OV injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 44 publications
1
58
0
Order By: Relevance
“…For reference, Table S2 also compares the best-fit parameters found herein to those previously found using a different algorithm and a slightly different metric of fit (35). Finally, Table S2 includes the 95% credible interval for each fit parameter, as calculated from the approximated posterior distributions (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For reference, Table S2 also compares the best-fit parameters found herein to those previously found using a different algorithm and a slightly different metric of fit (35). Finally, Table S2 includes the 95% credible interval for each fit parameter, as calculated from the approximated posterior distributions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this prior work, we used the best-fit parameters to address the question of the optimal treatment ordering when administering three doses of Ad/4-1BBL/IL-12 with three doses of the DC vaccine. We predicted that exactly one strategy, front loading the cytokine-bearing OVs (OV-OV-OV-DC-DC-DC), resulted in tumor eradication (35). However, upon further exploration, we found that the model displayed some unintuitive responses to altering the dosing order.…”
mentioning
confidence: 96%
See 3 more Smart Citations